Physiologically based pharmacokinetic modeling of tadalafil to inform pediatric dose selection in children with pulmonary arterial hypertension - Jessica Rehmel; Lisa Ferguson‐Sells; Bridget L. Morse; Baohui Li; Gemma L. Dickinson (Wiley, 2022)
Abstract Tadalafil, a phosphodiesterase 5 inhibitor, is being investigated as a treatment for pulmonary arterial hypertension (PAH) in children aged 6 months to less than 18 years. Tadalafil pharmacokinetic (PK) data in children less than 2 years old are unavailable, therefore a physiologically based pharmacokinetic (PBPK) model was developed to enable estimation of tadalafil doses in children less than 2 years old. The model was verified in adults and extended for use in children by modifying CYP3A‐mediated intrinsic clearance to include CYP3A7. To account for co‐dosing of the commonly prescribed moderate CYP3A4 inducer bosentan, predicted exposures were increased by a factor of 1.54 based on changes in exposure in adults with PAH. This factor was predictable using a bosentan PBPK model. The tadalafil model was verified in children aged greater than or equal to 2 years by comparing predicted and observed exposures. Tadalafil doses for children less than 2 years old were calculated as target area under the concentration curve from zero to 24 h (AUC0-24)/predicted AUC0-24, with target AUC0-24 of 10,000 ng*h/ml based on adult 40 mg single dose exposures determined in patients without bosentan background treatment. These doses were 2 mg, 3 mg, 4 mg, and 6 mg, respectively, for children aged birth to less than 1 month, 1 month to less than 6 months, 6 months to less than 1 year, and 1 to less than 2 years. Due to uncertainties in CYP maturation, a nonmechanistic steady‐state volume scalar, and lack of PK data in children less than 2 years old, accumulation of tadalafil to steady‐state in children less than 2 years was not verifiable. Safety of proposed doses is supported by postmarketing research and investigator‐led trials.